Respuesta :
Answer:
The equivalent expression is (2 / x ^ 3) * sqrt (2)
Step-by-step explanation:
We have sqrt 8 / x ^ 6
Rewriting the expression:
=sqrt (8 / x ^ 6)
=sqrt (2 * 4 / ((x ^ 2) * (x ^ 2) * (x ^ 2)))
=(2 / (x * x * x)) sqrt (2)
= (2 / x ^ 3) * sqrt (2)
We get finally
(2 / x ^ 3) * sqrt (2)
Answer:
[tex]\frac{2\sqrt{2}}{x^3}[/tex]
Step-by-step explanation:
[tex]\sqrt{\frac{8}{x^6} }[/tex]
To simplify the given expression we take square root for the top and bottom
[tex]\frac{\sqrt{8} }{\sqrt{x^6} }[/tex]
[tex]\sqrt{8} =\sqrt{4*2} =2\sqrt{2}[/tex]
[tex]\sqrt{x^6} =\sqrt{x^3*x^3} =x^3[/tex]
Replace it in our problem
[tex]\frac{2\sqrt{2}}{x^3}[/tex]